Safety analysis of sofosbuvir and ledipasvir for treating hepatitis C. (August 2015) - Fazel, Yousef; Lam, Brian; Golabi, Pegah; Younossi, Zobair
Abstract : Introduction: The approval ofsofosbuvir (SOF), a nucleotide analogue NS5B polymerase inhibitor, andledipasvir (LDV), a NS5A inhibitor, marked a new chapter in IFN and ribavirin-free treatment of hepatitis C virus (HCV). This drug reduces adverse events associated with IFN therapy. Areas Covered: The purpose of this paper is to evaluate the safety and efficacy of LDV/SOF. Clinical trials illustrating safety and efficacy of LDV/SOF are reviewed and compared to other IFN and ribavirin-free treatment options available. Expert Opinion: In trials enrolling more than 3000 patients, LDV/SOF is well tolerated with a good safety and side-effect profile in diverse cohorts, including previous direct-acting antiviral (DAA) treatment failures, liver transplant recipients, decompensated cirrhosis and HIV/HCV co-infection. As with all DAAs, the potential for drug–drug interactions must be carefully evaluated, as demonstrated by recent post-marketing reports of symptomatic bradycardia when LDV/SOF is co-administered with amiodarone. Currently, dose recommendations cannot be given for patients with advanced renal disease. Trials in this population are ongoing, more study is warranted. When surveying the DAA regimens available, efficacy, safety and tolerability of LDV/SOF is comparable or better, and LDV/SOF provides an option with convenient single-tablet, once daily, ribavirin-free dosing with relatively few significant drug–drug interactions.